2007
DOI: 10.1523/jneurosci.3926-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Blockade of Dopamine D1-Family Receptors in Nucleus Accumbens Core or Shell on Reinstatement of Heroin Seeking Induced by Contextual and Discrete Cues

Abstract: In humans, exposure to environmental contexts previously associated with heroin intake can provoke drug relapse, but the neuronal mechanisms mediating this relapse are unknown. Using a drug relapse model, we found previously that reexposing rats to heroinassociated contexts, after extinction of drug-reinforced responding in different contexts, reinstates heroin seeking. This effect is attenuated by inhibition of glutamate transmission in the ventral tegmental area and medial accumbens shell, components of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
312
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(347 citation statements)
references
References 63 publications
29
312
4
Order By: Relevance
“…We found that medial and lateral accumbens shell (but not core) SCH 23390 injections attenuate contextinduced reinstatement of heroin seeking (Bossert et al 2007). These findings are consistent with those of Hamlin et al (2007): context-induced reinstatement of alcohol seeking is associated with increased Fos (a neuronal activity marker) expression in accumbens shell, an effect reversed by systemic SCH 23390 injections.…”
Section: Pharmacology and Neuroanatomy Of Context-induced Reinstatementsupporting
confidence: 92%
“…We found that medial and lateral accumbens shell (but not core) SCH 23390 injections attenuate contextinduced reinstatement of heroin seeking (Bossert et al 2007). These findings are consistent with those of Hamlin et al (2007): context-induced reinstatement of alcohol seeking is associated with increased Fos (a neuronal activity marker) expression in accumbens shell, an effect reversed by systemic SCH 23390 injections.…”
Section: Pharmacology and Neuroanatomy Of Context-induced Reinstatementsupporting
confidence: 92%
“…AcbSh infusion of D 1 dopamine receptor antagonists attenuates renewal of heroin seeking (Bossert et al, 2007), whereas B/M infusions attenuate renewal of cocaine seeking (Fuchs et al, 2008). AcbSh neurons respond to stimuli associated with drug-availability (Ghitza et al, 2003), and increased c-Fos in the AcbShV is associated with renewal (Hamlin et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…Petrovich et al (2005) showed upregulated immediate early genes in LH-projecting neurons in orbitomedial PFC, BLA, and basomedial amygdala after presentation of a stimulus paired with food. A large number of forebrain afferents to LH have been implicated in renewal of drug seeking, including BLA, dmPFC (Fuchs et al, 2005), and AcbSh (Bossert et al, 2007;Fuchs et al, 2008). Different afferents may converge on LH as a final common pathway for reinstating extinguished reward seeking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once electrically evoked dopamine release was detected in the nucleus accumbens core, a layer of dental cement was applied to secure the electrodes in place and allowed to dry. We focused on the core region of the NAc because of previous evidence suggesting that the core is critically involved in modulating cue-driven behavioral responses, whereas the shell is more involved in modulating context-driven behavioral responses (Bossert et al, 2007;Chaudhri et al, 2009;Ito and Hayen, 2011).…”
Section: Surgerymentioning
confidence: 99%